2015
DOI: 10.1155/2015/924670
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity and Loss of Mitochondrial Membrane Potential Induced by Alkyl Gallates in Trypanosoma cruzi

Abstract: American trypanosomiasis or Chagas disease is a debilitating disease representing an important social problem that affects, approximately, 10 million people in the world. The main aggravating factor of this situation is the lack of an effective drug to treat the different stages of this disease. In this context, the search for trypanocidal substances isolated from plants, synthetic or semi synthetic molecules, is an important strategy. Here, the trypanocidal potential of gallates was assayed in epimastigotes f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
8
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 47 publications
(47 reference statements)
3
8
0
Order By: Relevance
“…The trypanocidal activity of gallic acid could be due to the presence of the extra hydroxyl group and its ability to form reactive oxygen intermediates in the parasite [19]. Although gallic acid showed trypanocidal activity in this study, interestingly, in other studies, gallic acid was inactive against other kinetoplastids such as Leishmania donovani and Trypanosoma cruzi [19, 20] and this could be due to the intracellular nature of these parasites. The amastigote forms of Leishmania and the amastigotes of Trypanosoma cruzi exists intracellularly in mammalian cells.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…The trypanocidal activity of gallic acid could be due to the presence of the extra hydroxyl group and its ability to form reactive oxygen intermediates in the parasite [19]. Although gallic acid showed trypanocidal activity in this study, interestingly, in other studies, gallic acid was inactive against other kinetoplastids such as Leishmania donovani and Trypanosoma cruzi [19, 20] and this could be due to the intracellular nature of these parasites. The amastigote forms of Leishmania and the amastigotes of Trypanosoma cruzi exists intracellularly in mammalian cells.…”
Section: Discussionmentioning
confidence: 62%
“…A fully functional mitochondrion will have an intact membrane potential leading to the internalization and the retention of the dye in the mitochondrion. In a defective or leaky mitochondrion, the membrane potential will be lost, and the dye will aggregate in the cytoplasm [20]. The generation of reactive oxygen species causes damage to the mitochondrion leading to a loss in its membrane potential [25].…”
Section: Discussionmentioning
confidence: 99%
“…Based on our proposition, Gly 2 treatment lead to repudiation of promastigotes further causing increased ROS generation whereas control parasites showed balanced redox homeostasis. Further, it has been reported that drug-induced loss in ∆Ψm is associated with cellular death in L. donovani, L. amazonensis and Trypanosoma cruzi [44]. ∆Ψm loss and ROS elevation are coupled events and act as crucial signals of necrosis [45].…”
Section: Discussionmentioning
confidence: 99%
“…Anti-pathogenic activity of alkyl gallates has been investigated in another eukaryote Trypanosoma cruzi, a causative agent of Chagas disease (Andréo et al, 2015). Results showed that longer-chain alkyl gallates, viz., nonyl, decyl, undecyl, dodecyl gallates, exhibited potent anti-trypanosomal activity, where loss of mitochondrial potential in T. cruzi could be one mechanism of anti-trypanosomal action of alkyl gallates (Andréo et al, 2015).…”
Section: Introduction (Continued)mentioning
confidence: 99%